Effect of Sepiolite-Loaded Fe2O3 on Flame Retardancy of Waterborne Polyurethane - Tong Xu; Di Qian; Yelei Hu; Yuanzhao Zhu; Yi Zhong; Linping Zhang; Hong Xu; Huaxin Peng; Zhiping Mao (Advances in Polymer Technology)
In this study, a kind of inorganic composite flame retardant (Sep@Fe2O3) was prepared by combining solution deposition and calcination methods using sepiolite microfiber material as carrier. This inorganic compound flame retardant was combined with waterborne polyurethane (WPU) through layer-by-layer method to prepare WPU composites. The SEM and EDS, TEM, and XRD were used to characterize the microscopic morphology and crystal structure of WPU composites. Thermogravimetric analysis tests confirmed the good thermal stability of WPU/Sep@Fe2O3 composites; at the temperature of 600°C, the carbon residual percentage of WPU/Sep, WPU/Fe2O3, and WPU/Sep@Fe2O3 composites is 7.3%, 12.2%, and 13.4%, respectively, higher than that of WPU (1.4%). Vertical combustion tests proved better flame-retardant property of WPU/Sep@Fe2O3 composite-coated cotton than noncoated cotton. The microcalorimeter test proved that the PHRR of WPU/Sep@Fe2O3 composites decreased by 61% compared with that of WPU. In addition, after combining with Sep@Fe2O3, the breaking strength of WPU increased by 35%.